KEAHLIAN PELAUT YANG HARUS DIMILIKI PERWIRA DEK DI KAPAL NIAGA - Ade Chandra Kusuma (Majalah Ilmiah Bahari Jogja, 2015)
In the world of the distribution industry is accepted as a commercial implementation of all business activities included in the transport of goods from the place of processing or fabrication to the place of sale to customers which include; warehousing, dosage control of finished goods, handling and packing materials, manufacture and delivery documentation, traffic and transport and post-sales services to customers.